Atorvastatin and fluvastatin are associated with dose‐dependent reductions in cirrhosis and hepatocellular carcinoma, among patients with hepatitis C virus: Results from ERCHIVES. Issue 1 (25th March 2016) - Simon, Tracey G.; Bonilla, Hector; Yan, Peng; Chung, Raymond T.; Butt, Adeel A.
Abstract : Statins are associated with delayed fibrosis progression and a reduced risk of hepatocellular carcinoma (HCC) in chronic hepatitis C virus (HCV). Limited data exist regarding the most effective type and dose of statin in this population. We sought to determine the impact of statin type and dose upon fibrosis progression and HCC in patients with HCV. Using the Electronically Retrieved Cohort of HCV Infected Veterans (ERCHIVES) database, we identified all subjects initiated on HCV antibody (anti‐HCV) therapy from 2001 to 2014, and all incident cases of cirrhosis and HCC. Statin use was measured using cumulative defined daily dose (cDDD). Multivariable Cox's proportional hazard regression models were used to examine the relationship between statin use and development of cirrhosis and HCC. Among 9, 135 eligible subjects, 1, 649 developed cirrhosis and 239 developed incident HCC. Statin use was associated with a 44% reduction in development of cirrhosis (adjusted hazard ratio [HR]: 0.6; 95% confidence interval [CI]: 0.53, 0.68). The adjusted HRs (95% CI) of fibrosis progression with statin cDDD 28‐89, 89‐180, and >180 were 0.74 (0.59, 0.93), 0.71 (0.59, 0.88), and 0.6 (0.53, 0.68), respectively. Mean change in FIB‐4 score with atorvastatin (n = 944) and fluvastatin (n = 34) was ‐0.17 and ‐0.13, respectively ( P = 0.04), after adjustment for baseline FIB‐4 score and established predictors of cirrhosis. Statin use was also associated with a 49% reduction in incident HCC (adjusted HR: 0.51; 95% CI: 0.36, 0.72). A similar dose‐response relationship was observed. Conclusion: In patients with chronic HCV, statin use was associated with a dose‐dependent reduction in incident cirrhosis and HCC. Atorvastatin and fluvastatin were associated with the most significant antifibrotic effects, compared with other statins. (Hepatology 2016;64:47–57)